Efektivitas Ekstrak Daun Kopasanda (Chromolaena Odorata L.) Sebagai Penangkal Efek Radikal Bebas Formulasi Tabir Surya - Hikmah Ramadana Nasution; Ida Hasmita; Eka Marya Mistar (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Kopasanda (Chromolaena Odorata L.) is a plant that contains flavonoid compounds in it where these compounds can act as natural antioxidants. This study aims to see the effectiveness of kopasanda leaf extract as a free radical scavenger in sunscreen formulations. Currently, the need for skin care is increasing, where the level of skin brightness is one indicator of skin health. Skin color when exposed to UV rays will change even if left to be exposed continuously which is worse can cause cancer. Kopasanda leaves are studied to contain ingredients rich in flavonoids such as polyphenol compounds that have a role as antioxidants in warding off free radicals. In proving this, it is necessary to test the antioxidant activity with the DPPH method, as well as apply it as a lotion product. Kopasanda leaf extract with the addition of ethanol solvent with varying concentrations of kopasanda leaf extract additives of 1%, 3%, 5%, and 7% with stirring times of 30 minutes, 60 minutes, and 90 minutes. The results of the study on antioxidant activity without adding a concentration of 0 were 124,845 ppm and the antioxidant activity with the addition of a concentration of 5% and 7% were 117,230 ppm and 114,201 ppm.